Review of Article 164 of the revised Treaty of Chaguaramas and products benefitting thereunder - Baker, Paul (2011)
This report identifies a number of findings which highlight the weaknesses of national governments, the secretariats and the private sector in addressing the constraints to promoting the Article 164 industries. It also highlights the fact that a number of products are benefitting from Article 164 when they would perhaps be better protected under Article 151 [which aims to protect sensitive industries] and other products which are not produced on any scale should be removed from the list altogether.